PENERIMAAN KONSUMEN TERHADAP KARAKTERISTIK MUTU KERUPUK IKAN JELAWAT (Leptobarbus hoevenii) - Gusta Damayana; Edison Edison; Sumarto Sumarto (Berkala Perikanan Terubuk, 2016)
This research was done to evaluate quality characteristic and consumer acceptance of river carp crackers added with river carp meat. The meat of river carp was taken from fresh river carp in cage aquaculture at Ranah, Kampar regency. Five groups of river carp crackers were made from tapioca flour (53,70%), wheat flour (5,97%), onion (1,79%), salt (1,49%), cake soda (0,30%), water (29,83%), sugar (0,89%) and egg (6,03%); then added the meat of river carp for each concentration 0%, 10%, 20%, 30% and 40%. River carp crackers were evaluated for sensory quality, consumer acceptance, proximate composition and flower power. The result indicated that the cracker was added by 30% river carp meat was most preferable. Moisture, protein, calcium, fat and flower power of the river carp cracker was 3,92%; 17,10%; 5,63mgCa/100g; 18,85% and 57,79% respectively.